Manajemen Sarana Dan Prasarana Pendidikan Di Sekolah Unggulan SD Bintang Madani - Zainudin, Ali; Badrudin, Badrudin (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
The purpose of this research is to ascertain how important the management of facilities and infrastructure is to improve student learning standards. With a library-based approach, this research uses a qualitative methodology. The findings show how important infrastructure management is for improving the teaching and learning standards of students at SD Bintang Madani. 1) Planning for facilities and infrastructure at SD Bintang Madani is carried out through meeting activities. 2) Procurement of facilities and infrastructure at SD Bintang Madani is carried out according to the results of supervision of existing facilities and infrastructure. 3) An inventory of facilities and infrastructure at SD Bintang Madani is carried out according to the established standard operating procedures. 4) The distribution of facilities and infrastructure at Bintang Madani Elementary School is carried out according to the provisions in the previous plan. 5) Maintenance of facilities and infrastructure at SD Bintang Madani, the school has appointed 9 education staff. 6) The removal of facilities and infrastructure at SD Bintang Madani is carried out for facilities and infrastructure that cannot be repaired. 7) Supervision of facilities and infrastructure at SD Bintang Madani is carried out by internal parties and in collaboration with external parties.